Persona development: Analyzing varying characteristics of slow learner context in relation to reading abilities - Mansor, Marzita; Wan Adnan, Wan Adilah; Abdullah, Natrah (2015)
Designing personalized interface for reading purpose to fulfill the needs of children with reading disabilities, especially the slow learner, is not an easy task.requires in depth knowledge of the children and their ability to read as well. Realizing that the basis for user-centered design is the knowledge of users and task, this study take an initial step by developing slow learner persona.Better understanding of the slow learner persona and reading scenario enable the designer to develop suitable personalized solution that can cater slow learner reading difficulties. This paper presents the development of slow learner persona in accordance with the principles of human-centered design (HCD).Data collected through interviews and observation of slow learner reading activity are analyzed and transformed into slow learner persona to be used as a reference in developing personalized reading application for slow learner children with reading difficulties. In particular, the slow learner persona presents as context templates to derive information needs of users in relation to reading ability to be used as vital elements for developing personalized reading application.